Profiles and interrelationships of functional soil microbiomes involved in phosphorus cycling in diversified agricultural land‐use systems - Minghui Li (Wiley, 2021)
Abstract Soil microbiomes play important roles in both transformation and utilization of phosphorus (P) in agroecosystems. By targeting at 18S rRNA, pqqC, and phoD genes, respectively, the community compositions of soil arbuscular mycorrhizal (AM) fungi and inorganic P‐solubilizing and organic P‐mineralizing prokaryotes were investigated across fields with annual crops or vegetables and orchards with peach trees or tea bushes in a common Agri‐technology Park, representing four typical agricultural land‐use types in Eastern China. Both annual crop and vegetable fields exhibited higher soil fertility and phosphatase activity, while both peach tree and tea bush orchards contained greater abundances of AM fungal and pqqC genes. Land‐use type also significantly affected the community compositions of soil AM fungi, and pqqC‐ and phoD‐harboring prokaryotes, with soil available P as the common driver for all functional groups above. Three main ecological clusters (modules) with distinctive interactive features, that is, synergistic, competitive, and inactive were observed in the co‐occurrence network comprised of the three groups involved in P‐cycling. The modules exhibited various distributions among the four land‐use types, and the correlations with soil pH, available P and K, and N:P were shown. Altogether, the results demonstrated the changes in gene abundances, diversity indices, community compositions, and interrelationships of functional groups involved in P‐cycling in response to distinct land‐use types, and highlighting the synergistic potential among groups to alleviate P deficiency.